Effects Of Government Policy, Employment Status, Organizational Culture, And Leadership Toward Self-Well-Being Mediated by Motivation on Non-Permanent Teachers and Staffs at Public Jhs Level of Bangka Regency - Inka Novia Tunggadewi; Reniati Reniati; Ari Agung Nugroho (Garuda Prestasi Nusantara Consulting, 2026)
This research analyzed the effects of government policy, employment status, organizational culture, and leadership on self-well-being, mediated by motivation, for non-permanent teachers and staff (GTT/PTT) at public JHS levels in Bangka Regency. This quantitative research approach took 62 GTT/PTT samples from the public JHS level in the Bangka regency. Then, the researchers collected the data using a questionnaire and analyzed it with Partial Least Squares-Structural Equation Modelling, PLS-SEM. The results indicated that government policy, organizational culture, and leadership have a positive and significant impact on the motivation and self-well-being of GTT/PTT. On the other hand, the employment status negatively and significantly influenced the motivation and self-well-being of GTT/PTT. The findings indicate that external factors, such as government policy, employment status certainty, organizational culture, and leadership, affect the self-wellbeing of GTT/PTT, rather than the internal factor of work motivation. The research theoretically contributes to the development of human resource management reviews within the education sector, as well as regional government and school considerations, to formulate policies that support the well-being and work motivation of GTT/PTT